Effects of a structured educational intervention on knowledge and emergency management in patients at risk for anaphylaxis. Issue 2 (February 2015) - Brockow, K.; Schallmayer, S.; Beyer, K.; Biedermann, T.; Fischer, J.; Gebert, N.; Grosber, M.; Jakob, T.; Klimek, L.; Kugler, C.; Lange, L.; Pfaar, O.; et al.
Abstract Background Structured educational programmes for patients at risk for anaphylaxis have not yet been established. Patients and caregivers often lack adequate skills in managing the disease. Methods To investigate effects of structured patient education intervention on knowledge, emergency management skills and psychological parameters in patients with previous episodes of anaphylaxis and caregivers of affected children 95 caregivers (11 male, 84 female, mean age 37 years) of affected children and 98 patients (32 male, 66 female, mean age 47.5 years) were randomly assigned to an intervention (IG) or control group (CG) in a multicentre randomized controlled trial. The IG received two 3‐h schooling modules of group education; the CG received standard auto‐injector training only. Knowledge of anaphylaxis and emergency management competence in a validated training anaphylaxis situation as main outcome measures as well as secondary psychological parameters were assessed at baseline and 3 months after intervention. Results In comparison with controls, the intervention led to significant improvement of knowledge from baseline to 3‐month follow‐up (caregivers: IG 3.2/13.2 improvement/baseline vs CG 0.7/12.6; P < 0.001; patients: IG 3.9/10.8 vs 1.3/12.6; P < 0.001). Moreover, emergency management competence was increased after intervention as compared to controls (caregivers: IG 8.6/11.2 vs CG 1.2/10.8; P < 0.001; patients: 7.1/11.0 vs 1.1/11.1; P < 0.001). Intervention showed significant reduction of caregiver anxiety (−1.9/8.4 vs −0.7/7.5; P < 0.05). There were no significant changes in the depression scores. Conclusion Structured patient education programmes may be beneficial in the management of anaphylaxis by increasing patients' empowerment to prevent and treat the disease.